Call to Teacher Leadership. - Mayers, R. Stewart, 1959- (Taylor and Francis, 2013)
The Call to Teacher Leadership demonstrates the many ways teachers can be leaders without having to opt out of the classroom full-time. It examines formal leadership positions - instructional coordinators, lead teachers, department chairs, etc. - as well as informal leadership roles - nurturing colleagues, supporting the instructional program, participating in decision making, etc. With practical examples and case studies, this book provides details about how teachers have participated in the leadership of their schools and districts. Examples come from elementary, middle, and high schools acr.